2019
DOI: 10.1038/s41598-019-52975-z
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence with Pseudomonas aeruginosa alters Staphylococcus aureus transcriptome, antibiotic resistance and internalization into epithelial cells

Abstract: Cystic fibrosis (CF) is the most common life-threatening genetic disease among Caucasians. CF patients suffer from chronic lung infections due to the presence of thick mucus, caused by cftr gene dysfunction. The two most commonly found bacteria in the mucus of CF patients are Staphylococcus aureus and Pseudomonas aeruginosa. It is well known that early-infecting P. aeruginosa strains produce anti-staphylococcal compounds and inhibit S. aureus growth. More recently, it has been shown that late-infecting P. aeru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 53 publications
(64 reference statements)
5
90
0
1
Order By: Relevance
“…This trophic specialization commonly leads to the slower growth of chronic isolates and thus less competitive 4 behavior regarding shared resources (16). Several independent studies observed this state of coexistence between S. aureus and P. aeruginosa isolated from chronic infections (10,15,17,18). Briaud et al recently demonstrated that this interaction pattern appears to be more frequent than expected.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…This trophic specialization commonly leads to the slower growth of chronic isolates and thus less competitive 4 behavior regarding shared resources (16). Several independent studies observed this state of coexistence between S. aureus and P. aeruginosa isolated from chronic infections (10,15,17,18). Briaud et al recently demonstrated that this interaction pattern appears to be more frequent than expected.…”
Section: Introductionmentioning
confidence: 94%
“…As schematized in Figure S1A, interaction state was determined for each pair by growth inhibition tests on Tryptic Soy Agar (TSA) and in liquid cultures (18). As previously described, coexistence was characterized by: (i) the absence of inhibition halo on agar tests, and (ii) similar growth in mono and co-cultures for 8 hours (18).…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 3 more Smart Citations